Kansas City [videorecording] : death by design (BBC, 2006)
BBC Active Video for Learning specially commissioned and created two new Disaster programmes, specifically intended to focus and inform you and your colleagues on issues relating to health and safety issues, crisis management and post-disaster supervision. Kansas City - Death by Design is the first of these programmes. Kansas City - Death by Design portrays the catalogue of horrific human error, architectural flaws and tragic occurrences that led to the deaths of over 100 people as two of the walkways in the Hyatt Regency hotel's atrium collapsed. Using events from history, Kansas City - Death by Design is a BBC instructional videos in the Disaster series (series4) providing essential health and safety training advice and warnings for all who watch.